PENGARUH SISTEM ADMINISTRASI PERPAJAKAN MODERN BERBASIS E-SAMSAT TERHADAP TINGKAT KEPUASAN PUBLIK PADA PEMERINTAH PROVINSI BALI - Putri, Ni Made Anggarani Nirmala Dewi Narendra; Prabawati, Ni Putu Anik; Winaya, I Ketut (CITIZEN CHARTER, 2022)
The level of public satisfaction with the government in the tax sector is still lacking as a result of several things such as the lack of transparency in tax management, hoaxes that spread through social media, tax officials who commit corruption, and most importantly the tax administration system which is still lacking. One of the programs from the Official Assessment System in Bali Province is Electronic Samsat or known as E-Samsat. E-Samsat is an information service for bills and online payments through banks. The existence of the urgency of public satisfaction in knowing the reputation of the Bali Provincial Government in the field of taxation, this study raises the title Effect of the Modern E-Samsat-Based Tax Administration System on the Level of Public Satisfaction in the Government with the aim of knowing the regression relationship in the E-Samsat-based Modern Tax Administration System on the level of Public Satisfaction in Bali Province. This study uses a quantitative type with associative-clausal method. Conclusions are drawn in the form of a relationship and influence of a modern administrative system based on E-Samsat on Public Satisfaction. The resulting effect of Modern Tax Administration System on the level of Public Satisfaction is a positive influence with the percentage reaching 79.7% and the rest are factors outside the Modern Tax Administration System. Indicators of Improvement of Human Resource Management have the best influence with every increase in the indicator by 1% it will give the effect of increasing the Public by 1.504, the indicator of Information and Communication Technology has the least influence with every increase in the indicator by 1% it will have the effect of increasing the Public of 0.335. This study rejects hypothesis 0 and accepts hypothesis 1, namely that there is an influence of the E-Samsat-based Modern Tax Administration System on the public level of government.